Comparison of the reproducibility of two cervical vertebrae maturation methods - Paulo Henrique da Rocha Duque; Rodrigo César Santiago; Rogério Lacerda dos Santos; Fernanda Ramos de Faria; Carolina de Sá Werneck; Robert Willer Farinazzo Vitral; Marcio Campos (Universidade Estadual de Campinas, 2022)
Aim: Facial orthopaedic treatments based on the stimulation or restrictions of craniofacial bone growth are more effective when carried out during the pubertal growth spurt. The aim of this cross-sectional study was to evaluate the reproducibility of two cervical vertebrae methods (CVM) with manual tracing and direct visual inspection. Methods: A sample of 60 lateral cephalometric radiographs (10 of each of the 6 CVM stages) was randomly selected from 171 records. 5 orthodontists classified these radiographs according to the skeletal maturation stage in 2002 and 2005, and the application of both methods was conducted by direct visual inspection and evaluation through manual tracing. Results: The average reliability of the two methods determination and the two forms of evaluation was substantial. The direct visual inspection evaluation showed the highest reliability and agreement interexaminer values for both methods, as well as the intraexaminers evaluation. Conclusion: The reproducibility of CVM method was substantial, indicating its clinical use to determine the skeletal maturity and the ideal moment for treatment execution.